Mice deficient in the mitochondrial branched-chain aminotransferase (BCATm) respond with delayed tumour growth to a challenge with EL-4 lymphoma - Ananieva, Elitsa A. (Br J Cancer, 2018)
BACKGROUND: The mitochondrial branched-chain aminotransferase (BCATm) is a recently discovered cancer marker with a poorly defined role in tumour progression. METHODS: To understand how a loss of function of BCATm affects cancer, the global knockout mouse BCATmKO was challenged with EL-4 lymphoma under different diet compositions with varying amounts of branched-chain amino acids (BCAAs). Next, the growth and metabolism of EL-4 cells were studied in the presence of different leucine concentrations in the growth medium. RESULTS: BCATmKO mice experienced delayed tumour growth when fed standard rodent chow or a normal BCAA diet. Tumour suppression correlated with 37.6- and 18.9-fold increases in plasma and tumour BCAAs, 37.5% and 30.4% decreases in tumour glutamine and alanine, and a 3.5-fold increase in the phosphorylation of tumour AMPK in BCATmKO mice on standard rodent chow. Similar results were obtained with a normal but not with a choice BCAA diet. CONCLUSIONS: Global deletion of BCATm caused a dramatic build-up of BCAAs, which could not be utilised for energy or amino acid synthesis, ultimately delaying the growth of lymphoma tumours. Furthermore, physiological, but not high, leucine concentrations promoted the growth of EL-4 cells. BCATm and BCAA metabolism were identified as attractive targets for anti-lymphoma therapy.